Dissimilar welding of ferritic stainless steel AISI 444 and AISI 316L austenitic stainless steel through the autogenous TIG process using pulsed current. - Isabel Ferreira de Barros (2014)
The use of stainless steels has intensified with the industrial demand growing, which extends its application for various sectors such as the oil and gas, desalination equipment in industry, sugar industry, among others. In that context, the use of ferritic stainless steels has grown in recent years on account of its excellent relationship between corrosion resistance and cost, and a great option in substitution of austenitic stainless steels. Intending to study the connection of dissimilar stainless steels by means of a welding process, this paper will lay the submit the ferritic stainless steel AISI 444 and AISI 316L austenitic stainless steel with TIG welding autogenous (without filler metal) with pulsed current. That union seeks to get a fused zone with better mechanical properties together with the correction of possible related to welding those steels problems, such as grain growth in ferritic steels, to which its refinement is possible through the use of pulsed current during the procedure. The choice of these two materials was based on the characteristics of each one separately for they possess closest properties, despite having different classifications, allowing the combined use of both, and thus ferritic act in order to partially replace the austenitic stainless steel in situations where the combination of high corrosion resistance and mechanical strength are not relevant. That action combined, and does not affect the characteristics of the set of negative way is to use lower cost benefit, because the presence of nickel austenitic stainless steels by more expensive finishes them. Thus, it is expected to provide, through this work, further deepening the respect of dissimilar welding between stainless steel AISI 444 ferritic and austenitic stainless steel AISI 316L, evaluating operational parameters such as the pulse of current and heat input on obtained microstructure and mechanical properties.